Investigation on ferroresonance due to power transformer energization in high voltage 400 kV transmission grid - Mateusz Polewaczyk; Sylwester Robak; Marcin Szewczyk (Archives of Electrical Engineering, 2019)
This paper presents a study on ferroresonance occurring in a high voltage 400 kV transmission grid due to energization of power transformer under no-load conditions. The system scenarios analyzed in the present paper are considered as critical for development and modernization plans as currently announced by the national grid operator in Poland. The PSCADsimulation modelwas developed and applied for several study cases of a system with double-circuit arrangement of a transmission line. It is shown that the ferroresonant oscillations can be initiated by two-phase switching operation of a line circuit breaker. The impact of the double-circuit length on the ferroresonance mode and severity is demonstrated with the use of the Poincaré map analysis and Short Time Fourier Transform. It is demon- strated that the length of the transmission line that is mutually coupled in the double-circuit arrangement has a significant impact on the ferroresonance occurrence and on its mode. As the ferroresonance can pose severe threat to the power system components due to the severe overvoltage and overcurrent oscillations, the analysis presented in this paper demonstrates the necessity of the ferroresonance analyses for any re-designed transmission system.